2014
DOI: 10.15809/irriga.2014v19n3p345
|View full text |Cite
|
Sign up to set email alerts
|

Impactos Do Nível De Irrigação E Da Cobertura Do Solo Na Cultura Do Tomateiro

Abstract: A água é um bem cada vez mais escasso e que também exerce grande influência na produtividade e na qualidade do tomateiro, tornando seu manejo um fator preponderante para a obtenção de maiores rentabilidades aliada a sustentabilidade. Avaliou-se nesse trabalho os efeitos de lâminas de irrigação (60%, 80%, 100%, 120% e 140% da ETc) e da cobertura do solo com filme plástico de polietileno preto sobre a produtividade, qualidade dos frutos e eficiência do uso da água (EUA) na cultura do tomateiro em campo, durante … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
2
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
3
7
2
8
Order By: Relevance
“…Water depths also interfered in the number of fruits per plant, with the water depth of 188 mm producing an average of 68 fruits (Table 3). This result differed from that obtained by Campagnol et al (2014), which observed that the use of soil plastic mulch and variation of the applied water depths did not influence the number of fruits per plant on the San Vito hybrid, with an average of 45 fruits, lower than the obtained in this study.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Water depths also interfered in the number of fruits per plant, with the water depth of 188 mm producing an average of 68 fruits (Table 3). This result differed from that obtained by Campagnol et al (2014), which observed that the use of soil plastic mulch and variation of the applied water depths did not influence the number of fruits per plant on the San Vito hybrid, with an average of 45 fruits, lower than the obtained in this study.…”
Section: Resultscontrasting
confidence: 99%
“…The applied water depth did not influence the mean fruit mass (Table 1). Results obtained in this study corroborate Campagnol et al (2014), which studied the effect of irrigation depths and did not observe water depths effect in the mean fruit mass as well, with an mean of 106.90 g fruit -1 for the "San Vito hybrid", close value to the obtained in this study. The commercial tomato for consumption "salad tomato" is valued mainly by its weight, being this an important attribute at commercial level.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…O manejo da irrigação deve ser realizado de modo a respeitar a demanda hídrica da cultura no decorrer de seu ciclo, e uma das formas é estimando a evapotranspiração da cultura (ETc) pelo tanque Classe A, porém, devido ao espaço limitado no interior de estufas frequentemente tem-se utilizado minitanques evaporímetros (CAMPAGNOL et al, 2014). De acordo com SOARES et al (2011) a irrigação controlada é importante para o aumento no rendimento do tomateiro, já que a cultura é sensível tanto à irrigação excessiva quanto insuficiente, tendo em vista que ocasionam problemas de ordem fisiológica e de crescimento.…”
Section: Introductionunclassified